(untitled) (Veterinary Science, 2017)
The article aims to review the epistemology of the extents and benefits that interdisciplinary has and also the disadvantages the people who form it have to overcome. Finally the author concludes with the benefits that interdisciplinary has in pursuit of the scientific knowledge and the positive effects on university education